THE ROLE OF SOCIAL MEDIA IN THE MARKETING STRATEGY IN THE HOTEL INDONESIA GROUP - Annisa, Rifa; Auliya, Anisatul (UI Scholars Hub, 2020)
This research aims to find out the role of social media such as Instgaram, Facebook and Website in implementing marketing strategies at Hotel Indonesia Group. Social Media is very helpful for Hotel Indonesia Group to promote therir product, because with social media Hotel Indonesia Group can attract social media users to stay at hotels under the Hotel Indonesia Group. The research method was qualitative methods. All the datas collection technique was carried out by interview and direct observation in the research object. This research was conducted from February 2020 to April 2020. The results of this study that the most popular social media by Hotel Indonesia Group consumers is Instagram. Hotel Indonesia Group manages social media to attract consumers' interest by providing creative and informative contents. From the results of interviews the importance of social media for the promotion of Hotel Indonesia Group is very important because it helps increase the number of potential customers.